1984
DOI: 10.1042/bj2220631
|View full text |Cite
|
Sign up to set email alerts
|

Rapid kinetic analysis of the bile-salt-dependent secretion of phospholipid, cholesterol and a plasma-membrane enzyme into bile

Abstract: Isolated rat livers were perfused under 'one-pass' conditions and bile was collected at 1 min intervals. After 1 min pulse, taurocholate appeared in the collected bile within 2 min, peak output occurring 2 min later. In contrast, the increased output of phospholipids and cholesterol was slower, peak output occurring 6-11 min after the original pulse of taurocholate. These results suggest that mixed micelles cannot be formed inside the cell or during passage of bile salts through the membrane, since bile salt a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

1987
1987
1995
1995

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 42 publications
(50 reference statements)
2
43
0
Order By: Relevance
“…These studies have shown that bile acid secretion precedes cholesterol and phospholipid secretion ( Fig. 3) [64], further suggesting a different mode for bile acid entry into the canaliculus from that of cholesterol and phospholipid. An insight into the possible intracellular mechanism for biliary lipid interaction is provided by studies showing that administration of substances such as colchicine and vinblastine, both known to inhibit microtubular function and hence vesicle movement inside the hepatocyte, reduce cholesterol and phospholipid secretion .…”
Section: Biliary Lipid Couplingmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have shown that bile acid secretion precedes cholesterol and phospholipid secretion ( Fig. 3) [64], further suggesting a different mode for bile acid entry into the canaliculus from that of cholesterol and phospholipid. An insight into the possible intracellular mechanism for biliary lipid interaction is provided by studies showing that administration of substances such as colchicine and vinblastine, both known to inhibit microtubular function and hence vesicle movement inside the hepatocyte, reduce cholesterol and phospholipid secretion .…”
Section: Biliary Lipid Couplingmentioning
confidence: 99%
“…As they pass across the membrane, or once they are in the canaliculus, bile acids solubilize cholesterol and phospholipid from the membrane. The observation that bile acids reach the canaliculus ahead of cholesterol and phospholipid in rapid kinetic experiment in the rat favours the second mechanism [64]. The increased number of vesicles observed at the canalicular pole of the hepatocyte during bile acid loading [90,91] may be interpreted as resupply of lipid carriers 'queuing up' next to the membrane exposed to the detergent effect of bile acid.…”
Section: Biliary Lipid Couplingmentioning
confidence: 99%
“…Although the secretion of bile salts, biliary phospholipids, and cholesterol occur via separate processes (39), the former is required for the latter to occur (31). As all amphiphilic molecules, bile salts tend to self-associate in water with increasing concentration (44).…”
Section: Fig 4 Effect Of Increasing Concentrations Of Triton X-100 mentioning
confidence: 99%
“…However, the observation that the rate of secretion of bile salts and biliary lipids are intimately related (29) has suggested that bile salts may also play a direct positive regulatory role in the transhepatic movement of biliary lipids (31). The mechanism responsible for such a promoting effect of bile salts remains unclear, but it has alternatively been proposed to involve direct solubilization of PC from the canalicular membrane (31,32), modulation of either phospholipid biosynthesis (33) or of intracellular trafficking of PC-rich vesicles from the endoplasmatic reticulum or the Golgi apparatus (34,35), or finally through direct activation of a PC transporter (Mdr2) in the canalicular membrane (23,24). The aim of the present study was to determine if and how bile salts such as taurocholate may regulate the activity of the Mdr2 PC translocase.…”
mentioning
confidence: 99%
“…In many studies a clear-cut relation has been observed between the secretion rate of bile salts and biliary lipids (7)(8)(9). Because of the detergent activity of the micellar bile salt concentrations in the canaliculus, it is generally assumed that bile salts act at this level to solubilize lipids from the membrane and indirect evidence for this assumption exists (10,11). However, bile salts may also promote the transhepatic flux of biliary lipids at other levels, like phospholipid synthesis (12) and intracellular transport via lipid vesicles (13,14) and/ or via phosphatidylcholine (PC)' transport protein (15,16).…”
Section: Introductionmentioning
confidence: 99%